The Role Of Ultrasound In Assessment Of Middle Cerebral Artery In Third Trimester In Pakistani Population - Bibi, Riffat; Ririe MD, Avrina Kartika; Alabi, Temidayo Abiodun; Obono, Godwin Ibiang; Ali Baig, Mirza Mohammad; Fatima, Zareen; Ayesha, Sadaf; Aftab, Syeda Kiran (Journal of Neonatal Surgery, 2025)
INTRODUCTION:Thepurposeof this study was to assess the Doppler indices (Pulsatility Index, Resistive Index and systolic to diastolic ratio) of fetal middle cerebral artery in normal pregnancies with gestation age from 27 to 40 weeks. In this study, the trends of Doppler flow velocity indices were determined. METHODS:Inthiscross sectional study, 100 normal pregnant women with gestational age between 27-40 weeks of pregnancy were evaluated by Doppler ultrasound for the assessment of three Doppler indices ( PI, RI and S/D ratio) for middle cerebral artery. RESULTS:Allthestudied Doppler parameters i.e. resistive index, pulsatility index and systolic to diastolic ratio of middle cerebral arteries decreased continuously in a parabolic pattern with the increase in gestational age. There was a significant correlation between MCA-PI, RI, S/D ratio and gestational age (<0.001). The values obtained were statistically significant